A ranking of critical competencies for shore-based maritime logistics executives in the digital era - Li, Xue (2022)
The globalisation and digitalisation trends trigger a demand for maritime logistics companies to continuously review the competency requirements of employees to enhance organisational performance. Therefore, this paper focuses on extending the business, logistics and management competency framework to identify and rank emerging critical competencies. Four key competencies and eighteen sub-competencies were identified and structured, anchored on the proposed business, logistics, management and digitalisation competency framework. A total of 42 responses from maritime logistics companies were collected through a questionnaire survey. The data collected were analysed using the fuzzy analytic hierarchy process. The results indicate that the key competencies, in descending order of importance, are business skills, logistics skills, management skills, and digitalisation skills. This research enriches the stream of literature on competency framework by highlighting digitalisation skills and updating the requirements of competencies maritime logistics executives in the era of digitalisation. Additionally, this research implicates policy implications regarding the strategic management of human resources of maritime logistics companies.